THE INFLUENCE OF COLD ROLLING TREATMENT ON THE SS 316L SURFACE PROPERTIES - Majid, Aulia; Palmiyanto, Martinus Heru (Department of Mechanical Engineering Education, 2024)
The biomedical field is increasingly developing with the creation of biomaterial dental crown products that can be used if teeth are damaged from an aesthetic perspective. 316L stainless steel is a biomaterial because it has good corrosion resistance and high mechanical characteristics. However, the corrosion resistance and mechanical strength of 316L stainless steel still need to be improved so that it can be a better dental crown material. This research objective is to increase the mechanical value of 316L stainless steel by cold rolling treatment. Variations in reducing thickness by cold rolling consist of 0%, 5%, and 12%. After that, the specimen will be tested for Vickers hardness on the specimen surface and wettability. The results obtained after the treatment were carried out that the greater the variation in reducing the thickness of the specimen, the greater the Vickers hardness value. However, in the wettability test, the contact angle value decreased along with increasing variations in thickness reduction. The increase in surface hardness value is due to the granules becoming denser due to the influence of cold rolling. This reduces the contact angle value so that the value of all variations becomes less than 90Ëš.